Uma proposta para licenciatura em matemática por meio dos sólidos de Platão - GUEDES, Clecilma Monteiro (2024)
The general objective of this work is to exercise the geometric construction and planning of solids, aiming to develop mathematical perception, focusing on reading the geometric structure of Plato's solids. The methodology is characterized as a scientific investigation, a bibliographical research model with a qualitative approach, divided into four chapters (i) initially provides a brief history of geometry with emphasis on geometric solids – pyramid and prisms, (ii) then emphasizes the panorama history of Plato's solids and their planning, (iii) supports the theoretical contributions, including LORENZATO (1995), SCOLARO (2008), SILVA (2014) also based on the book on spatial geometry by the authors OSVALDO DOLCE AND JOSÉ NICOLAU POMPEO ( 2013), in addition to the contribution of GOMES (1997), in his doctoral thesis describing plane geometry through the “dynamics of geometric thinking, also complying with BNCC (2018), in its competencies and skills for the 7th year of teaching fundamental (iv) addresses the educational product with the construction and planning of the cube and its analysis based on the geometric perception of its components. This study is still in the construction phase for TCC4 for mathematics graduates, and it is expected that the proposal will reach classrooms as an alternative to promote better understanding of mathematical content. Therefore, it is important that teachers are always innovating methodologies and selecting teaching resources, capable of offering students a more meaningful, personalized and stimulating approach, making mathematics a more enjoyable subject.